MOTIVATION AND STIMULATION SYSTEM OF THE PERSONNEL OF INDUSTRIAL ENTERPRISES - Klymchuk, A.O. (The actual problems of regional economy development, 2016)
This article is devoted to the problems of studying the system of motivation and stimulation of personnel at the industrial enterprises, which are important in today's conditions. The purpose of the study is a detailed analysis of system characteristics and motivation of personnel at the enterprises. It is proved that the enterprise's management must constantly deal with the improvement of the system of motivation and stimulation of personnel, that should be adapted to the new conditions for the market functioning. The author notes that the system of motivation and stimulation at the industrial enterprises is effectively connected with the problem of production activities at the enterprise and the final results of its operations increasing and the living standards of workers improving. In the article the basic functions (attracting qualified specialists, preservation groups of professionals within the required time limit), which must perform a system of motivation and stimulation of the personnel at the enterprise are determined. The main tasks that are necessary to ensure the desired level of labor activity of personnel are formed: determining a set of values ​​that should form the basis of personnel motivation; needs formation of each employee, his interests and capabilities of pleasure; specification of the types of work that require the enterprise and that it is advisable to motivate; labour organization so as to convince the employee's ability to satisfy its interests; coordination of certain types of worker with a set of values ​​and preferences; clarify the motives, interests and values ​​when hiring an employee at the enterprise. In order, to form the control system of motivation and stimulation, the need for the following conditions are stressed: availability of complete and accurate information about equipment management; the need to have permanent representation on the status and dynamics of the motivational orientation of personnel; carefully tracking the socio-economic impact of management decisions and the ability to predict. Based on the experience of many countries found that traditional methods of collecting data on the motivational and stimulating orientation personnel will not meet the needs of management practices, but because each enterprise proposed to introduce a system of motivation and stimulating monitoring, the main purpose of which is to create a new information base for decision making in motivation and stimulation of employees. Such monitoring should be directed to continuous monitoring and control of personnel motivating and encouraging to its rapid diagnosis and assessment of the dynamics, making qualified management decisions in order to improve production efficiency. On the basis of the research the key principles that should be based on the motivation system and incentives of personnel at the enterprise are identified: consistency; complexity; apolitical; frequency; production-territorial approach. The author made a comparative analysis of national systems of incentives and motivation of enterprises, which include the following: a system of financial incentives and incentives for the labor input; system management purposes; theoretical model of financial motivation and stimulation; the incentive and motivation, which are focused on business value – participation in ownership and option programs. Based on the studies, the system of incentives and motivation uses only the first part – the financial and economic motives and incentives, but incentives such as professional, labor, prestige and social status, as well as the motives and incentives related to career in these systems are the rather weak figure, which is also a lack of national systems of motivation and stimulation of labor personnel. The article notes that the success of the enterprise depends on the optimal combination of two components: the welfare of employees and maintain the efficiency of the production process. It is proved that the most effective system of motivation and stimulation of work is a combination of financial incentives and promotion of professional knowledge, high level of expertise aimed at achieving this goal, finding new ways to organize and manage the enterprise. JEL: M 12